Simulation of Semiconductor Processes and Devices 2007
DOI: 10.1007/978-3-211-72861-1_25
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Shear Strain and Quantum Confinement on <110> Channel nMOSFET with High-Stress CESL

Abstract: Numerical study in conjunction with comprehensive bending experiments has demonstrated that (100)-Si has the optimum channel direction along 110 in terms of the device performance of strained 65nm-node nMOSFETs with Contact Etch Stop Layer (CESL), and that both the shear strain component and the quantum confinement effect play an important role in this superiority.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…6(c) and 6(f), it can be observed that a compressive CESL induces tensile vertical stress ( z ) and that the removal of gate-top SiN decreases the magnitude of z from 0.54 to 0.25 GPa. In the device simulation, inversion layer mobility was calculated using a strain-dependent two-dimensional band structure, 14,15) which is available on Sentaurus Device. Figure 7 shows calculated mobility enhancement factors against channel stress for electrons and holes.…”
Section: Simulation Analysismentioning
confidence: 99%
“…6(c) and 6(f), it can be observed that a compressive CESL induces tensile vertical stress ( z ) and that the removal of gate-top SiN decreases the magnitude of z from 0.54 to 0.25 GPa. In the device simulation, inversion layer mobility was calculated using a strain-dependent two-dimensional band structure, 14,15) which is available on Sentaurus Device. Figure 7 shows calculated mobility enhancement factors against channel stress for electrons and holes.…”
Section: Simulation Analysismentioning
confidence: 99%